Local contractility and systolic function of left ventricular myocardium at rest and during cold stress test in patients with acute myocardial infarction - V. R. Veber; M. P. Rubanova; K. A. Antonov; S. V. Zhamylova (Кардиоваскулярная терапия и профилактика)
Aim. To examine the changes in left ventricular (LV) local contractility (LC) and systolic function at rest and during cold stress test in patients with acute myocardial infarction (AMI).Material and methods. The study included 67 AMI patients (mean age 56,41±1,06 years). The standard echocardiography examination took place at Day 10 after acute coronary syndrome (ACS) development. LC analysis was based on dividing LV into 16 segments.Results. With similar baseline LC and global contractility (GC), cold stress test identified various reactions in AMI patients, which might reflect various mechanisms for each reaction type. In groups 1 and 2, cold stress test causeddifferent two6phase reactions. At the same time, in Group 1, negative inotropic response and decreased LC were observed; in Group 2, both LC and GC inotropic effects were positive. Group 3 was characterized by unchanged LV LC. Younger AMI patients (40-49 years) typically demonstrated reaction 1, with reduced LC and "early" angina clinics. In older ages, reaction 2, with improved LC and increased LV volume at rest, was more typical. Cold stress test reaction, described by decreased LV LC, is associated with poor prognosis, due to high frequency of recurrent ACS (33,3%). Conclusion. Cold stress test could be used for prognosis assessment in AMI patients.